Left-handed metamaterial-inspired unit cell for S-Band glucose sensing application - Islam M.T.; Hoque A.; Almutairi A.F.; Amin N. (MDPI AG, 2023)
Computer software; Glucose; Medical problems; Metamaterials; Microwave sensors; Sensors; Computer simulation technology (CST); Experimental verification; Finite integration technique; Glucose concentration; Left handed metamaterial; Parametric -analysis; Sensing characteristics; Transmission coefficients; Solution mining; glucose; water; chemistry; computer simulation; genetic procedures; human; isolation and purification; microwave radiation; procedures; software; Biosensing Techniques; Computer Simulation; Glucose; Humans; Microwaves; Software; Water